Ethnic and gender trends at the annual British Association of Urological Surgeons (BAUS) meeting: A review of BAUS programmes over a 13-year period (2009–2021). (May 2023) - Massella, Virginia; Sinha, Mriganka; Pietropaolo, Amelia; Geraghty, Robert; Cresswell, Miss Jo; Philip, Joe; Shrotri, Nitin; Somani, Bhaskar K
Objective: In this paper, we wanted to review the annual British Association of Urological Surgeons (BAUS) programme to analyse the female and ethnic minority (EM) representation and find out whether there is ethnic and gender disparity, and if it does reflect the reality of the workforce. Methods: To investigate gender and EM representation, we requested data for BAUS annual meetings over a 13-year period (2009–2021). All speakers and chairpersons for all four sub-sections including Endourology, Oncology, Andrology and Female, Neurological and Urodynamic urology (FNUU) were collated. We also looked at the geographic distribution of the speakers (London area, rest of England, Scotland, Northern Ireland and Wales). Data were analysed separately before and after the COVID-19 pandemic (cut-off March 2020), as in the latter 2 years, the meeting was held virtually. Results: A total of 2569 speakers (range: 135–323 speakers/year) were included in our analysis and 2187 (85%) speakers were from the United Kingdom. Of the UK speakers, more than three-quarters (76.6%, n = 1676) were males and females of White ethnicity and (23.4%, n = 511) were EM. The vast majority of speakers throughout the years were males (86%, n = 1891) with only 14% ( n = 296) females regardless of their origin and ethnicity. The presence of EM females was only 1.9% ( n = 43). The percentage of female representation rose consistently over time from 6.7% ( n = 8) in 2009 to 21.1% ( n = 44) in 2020, suggesting an upward trend. Regional distribution showed 31%, 63%, 3.6%, 1.6% and 0.2% from London, Rest of England, Scotland, Wales and Northern Ireland, respectively. Both gender and EM representation doubled in the last 2 years during the pandemic ( p < 0.001). Conclusion: Annual BAUS meetings have seen a higher proportion of ethnic and gender representation in recent years. However, considering the workforce within urology, more needs to be done to address this historical disparity. Hopefully, the BAUS 10-point programme will provide a framework for addressing Equality, Diversity and Inclusion issues related to this bias. Level of evidence: Not applicable.